Inovasi Sistem E-Kasir untuk Meningkatkan Kinerja Usaha KUD Sawit Jaya - Fina Nasari; Andri Nofiar. Am; Antoni Pribadi; Fitri; Fenty Kurnia Oktorina; Muhammad Ridwan; Slamet Triyanto; Niken Ellani Patitis; Nina Veronika; Nur Asma Deli (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The Sawit Jaya Village Unit Cooperative (KUD) in Tapung District, Kampar Regency, Riau still uses a manual cashier system in the sales transaction process, which is time-consuming and labor-intensive. Therefore, innovation is needed by building an electronic cashier system that can improve the performance of the Sawit Jaya KUD business. The aim of this community service is to improve the effectiveness and efficiency of the sales transaction process of the Sawit Jaya KUD by implementing an electronic cashier system. The methods used in this community service include discussions, data collection, system design, system development, system implementation, training, and report writing. The results of this community service show that the electronic cashier system has successfully improved the performance of the Sawit Jaya KUD business and can help in producing more accurate and efficient sales reports. Thus, the implementation of an electronic cashier system can be a solution to improve the business performance of the Sawit Jaya KUD.